Fashion and handbags at the Helen Keller de Ribeirão Preto-SP school (Revista de Ensino em Artes, Moda e Design, 2020)
The project “History, memory and blindness: contributions from the School for the Blind Hellen Keller (1954-1990) from Ribeirão Preto to education”, approved by FAPESP under number 2017q23240-8, coordinated by Prof. Dr. Daniela Leal and other professors from the University Center Moura Lacerda received a large photo- graphic collection, in which some images are from bazaars and fairs held in the 1960s, carrying fashion products and handicrafts developed by the students of the scho- ol. The present research project has the objective of describing some details of the photos received, telling about the works developed, through exploratory descriptive and qualitative research, with the intention of bringing to light that part of history about inclusive education in our city. This study has brought about the possibility of knowing the universe of the visually impaired, especially the students from the Helen Keller School. In the images, it is possible to observe several products developed and marketed by the school, such as clothes (skirts, blouses, dresses), handbags, dish clo- ths, aprons, crocheted and knitted items, dolls, as well as decorated Christmas trees, among others. The school also motivated their students to develop manual skills in order to create opportunities, both for labor market as well as for social inclusion since the 1960s. The bibliographical survey and all this research contributed to unders- tand visual handicapped people, their form of thinking, acting and developing skills, showing that those students have the capacity to learn and become independent, provided that opportunities are offered.
Keywords: fashion; crafts; photograpy; visually handicapped people; Helen Keller School